Fermentable carbohydrate stimulates FFAR2-dependent colonic PYY cell expansion to increase satiety - Brooks,L; Viardot,A; Tsakmaki,A; Stolarczyk,E; Howard,JK; Cani,PD; Everard,A; Sleeth,ML; Psichas,A; Anastasovskaj,J; Bell,JD; Bell-Anderson,K; et al. (Molecular Metabolism, 2016)
ObjectiveDietary supplementation with fermentable carbohydrate protects against body weight gain. Fermentation by the resident gut microbiota produces short-chain fatty acids, which act at free fatty acid receptor 2 (FFAR2). Our aim was to test the hypothesis that FFAR2 is important in regulating the beneficial effects of fermentable carbohydrate on body weight and to understand the role of gut hormones PYY and GLP-1. MethodsWild-type or Ffar2-/-mice were fed an inulin supplemented or control diet. Mice were metabolically characterised and gut hormone concentrations, enteroendocrine cell density measurements were carried out. Intestinal organoids and colonic cultures were utilised to substantiate the in vivo findings.ResultsWe provide new mechanistic insight into how fermentable carbohydrate regulates metabolism. Using mice that lack FFAR2, we demonstrate that the fermentable carbohydrate, inulin, acts via this receptor to drive an 87% increase in the density of cells that produce the appetite-supressing hormone peptide YY (PYY), reduce food intake and prevent diet-induced obesity. Conclusion Our results demonstrate that FFAR2 is predominantly involved in regulating the effects of fermentable carbohydrate on metabolism and does so, in part, by enhancing PYY cell density and release. This highlights the potential for targeting enteroendocrine cell differentiation to treat obesity.